Relationship between Pyruvate Kinase Activity and Cariogenic Biofilm Formation in Streptococcus mutans Biotypes in Caries Patients - Krzyściak, Wirginia; Papież, Monika; Jurczak, Anna; Kościelniak, Dorota; Vyhouskaya, Palina; Zagórska-Świeży, Katarzyna; Skalniak, Anna (Frontiers in Microbiology, 2017)
Streptococcus mutans (MS) and its biotype I are the strains most frequently found in dental plaque of young children. Our results indicate that in children pyruvate kinase (PK) activity increases significantly in dental plaque, and this corresponds with caries progression. The MS strains isolated in this study or their main glycolytic metabolism connected with PK enzymes might be useful risk factors for studying the pathogenesis and target points of novel therapies for dental caries. The relationship between PK activity, cariogenic biofilm formation and selected biotypes occurrence was studied. Streptococcus mutans dental plaque samples were collected from supragingival plaque of individual deciduous molars in 142 subjects. Pyruvate kinase activity was measured at different time points during biofilm formation. Patients were divided into two groups: initial stage decay, and extensive decay. Non-parametric analysis of variance and ANCOVA were used to determine the connections between Streptococcus mutans levels, PK activity and dental caries biotypes. A total of 143 strains were derived from subjects with caries. Biotyping data showed that 62, 23, 50, and 8 strains were classified as biotypes I, II, III, IV, respectively. PK activity in biotypes I, II and IV was significantly higher in comparison to that in biotype III. The correlation between the level of S. mutans in dental plaque and PK activity was both statistically significant (p<0.05) and positive. The greater the level of S. mutans in the biofilm (colony count and total biomass), the higher the PK activity; similarly, a low bacterial count correlated with low PK activity